Chlamydomonas FBB18 is a ubiquitin-like protein essential for the cytoplasmic preassembly of various ciliary dyneins - Ryosuke Yamamoto; Yui Sahashi; Rieko Shimo-Kon; Miho Sakato-Antoku; Miyuka Suzuki; Leo Luo; Hideaki Tanaka; Takashi Ishikawa; Toshiki Yagi; Stephen M. King; Genji Kurisu; Takahide Kon (Proceedings of the National Academy of Sciences, 2025)
Motile cilia are organelles found on many eukaryotic cells that play critical roles in development and fertility. Human CFAP298 has been implicated in the transport/assembly of ciliary dyneins, and defects in this protein cause primary ciliary dyskinesia. However, neither the exact function nor the structure of CFAP298 have been elucidated. Here, we took advantage of Chlamydomonas , a ciliated alga, to study the structure and function of FBB18, an ortholog of CFAP298. Multiple ciliary dyneins were greatly reduced in cilia of Chlamydomonas fbb18 mutants. In addition, we found that both the stability of ciliary dynein heavy chains (HCs) and the association between HCs and intermediate/light chains (IC/LCs) are greatly reduced in fbb18 cytoplasm, strongly suggesting that FBB18 functions in the cytoplasmic assembly (the so-called “preassembly”) of dynein complexes from HC/IC/LCs. Furthermore, X-ray crystallography revealed that FBB18 forms a bilobed structure with globular domains at both ends of the molecule, connected by an α-helical bundle. Unexpectedly, one globular domain shows high similarity to ubiquitin, a small protein critical for the modification of a variety of protein complexes, and this ubiquitin-like domain is indispensable for the molecular function of FBB18. Our results demonstrate that FBB18, a specialized member of the ubiquitin-like protein family, plays a critical role in dynein preassembly, most likely by mediating diverse interactions between dynein HCs, molecular chaperone(s), and other preassembly factor(s) using the ubiquitin-like domain as well as other regions, and by facilitating the proper folding of dynein HCs.